Durability Performance of Polymer Composite Reinforced with Ceiba pentandra Wood Particles - Aina Kehinde Sesan; Olaniran Samuel Oluyinka; Falemara Babajide Charles; Bolarinwa Olayiwola Yetunde; Owolabi Temitope Olayemi; Olufemi Babatola (Journal of Building Materials and Structures)
The study investigated the effects of Coptotermes curvignathus termites on the durability and strength properties of wood plastic composites produced from recycled polythene bags and Ceiba pentandra wood particles. The wood particles were proportionately mixed with the polyethylene powder at ratios 40/60, 50/50 and 60/40 (w /w dry basis). The composites were produced using the single screw extruder and compounding method. Some of these composites were exposed to termite attack (Coptotermes curvignathus) attack at a timber graveyard. The composite samples, both unexposed and exposed to termite infestation, were subjected to durability and strength assessment tests. The results revealed composite board densities ranging from 781.0 kg/m3 to 810.6 kg/m3. Strength values ranged from 1087.8 N/mm² to 4320.0 N/mm² for flexural modulus, 43.7 N/mm² to 59.1 N/mm² for flexural strength, and 18.4 N/mm² to 32.6 N/mm² for compressive strength. The wood polyethylene composite made at 50/50 ratio had the lowest values for all properties tested both before and after termite exposure. The wood/polyethylene ratio significantly influence the weight, density, flexural modulus and compressive strength of the composites after termite exposure under a tropical climate. This study concluded that wood polyethylene composite (WPC) reinforced with Ceiba pentandra particles are highly durable. Specifically, WPC produced at a 40/60 wood/plastic ratio is recommended for structural applications in termite-prone areas, as it met the certified standard values of < 3.52 from SNI 01-7207-2006 and ASTM D3345 for graveyard tests.